Anti-epileptic effect of 16-O-acetyldigitoxigenin via suppressing mTOR signaling pathway - Tu, Wenjing; Qian, Sheng (Cellular and Molecular Biology, 2019)
Epilepsy is a common chronic disease of the central nervous system that can last for years or even decades, causing serious adverse effects on the body, mind, and psychology of patients. Traditional antiepileptic drugs can effectively control seizures, but because of large individual differences, serious adverse reactions, narrow therapeutic window and other shortcomings, more effective, new treatment drugs are looked for. Streptocaulon griffithii is a plant of Asclepiadaceae. 16-O-acetyldigitoxigenin (ACE) is a strong cardiac glycoside isolated from methanol extract of Streptocaulon griffithii. The aim of this study was to investigate the antiepileptic effect of ACE on Pilocarpine (Pilo) induced epilepsy in mice, and to explore the effect of mTOR signaling pathway on its antiepileptic effect. The results showed that ACE had antiepileptic and neuroprotective effects on Pilo induced epilepsy mice. ACE attenuates Pilo induced seizures by inhibiting the activation of p-mTOR/p-70S6K pathway, and inhibits Pilocarpine induced brain damage by inhibiting mTOR signaling pathway. These results suggest that ACE has a promising future in the treatment of epilepsy and other nervous system diseases.